2015
DOI: 10.3389/fpls.2015.00995
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Temperature Differentially Influences Effector-Triggered Immunity Outputs in Arabidopsis

Abstract: Pseudomonas syringae is a Gram-negative bacterium that infects multiple plant species by manipulating cellular processes via injection of type three secreted effectors (T3SEs) into host cells. Nucleotide-binding leucine-rich repeat (NLR) resistance (R) proteins recognize specific T3SEs and trigger a robust immune response, called effector-triggered immunity (ETI), which limits pathogen proliferation and is often associated with localized programmed cell death, known as the hypersensitive response (HR). In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(67 citation statements)
references
References 35 publications
3
64
0
Order By: Relevance
“…In addition, environmental factors such as temperature may interact with host resistance influencing the fitness of Avr3a in P. infestans . Temperature is one of the most important environmental parameters crucially impacting many aspects of host–pathogen interactions including host susceptibility (Menna, Nguyen, Guttman, & Desveaux, 2015), pathogen density (Mikkelsen, Jørgensen, & Lyngkjær, 2015), and effector gene expression (Banta et al., 1998). The hypothesis of temperature‐mediated Avr3a fitness is supported by significant associations of isoform frequency with the mean annual temperature in the sample sites (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, environmental factors such as temperature may interact with host resistance influencing the fitness of Avr3a in P. infestans . Temperature is one of the most important environmental parameters crucially impacting many aspects of host–pathogen interactions including host susceptibility (Menna, Nguyen, Guttman, & Desveaux, 2015), pathogen density (Mikkelsen, Jørgensen, & Lyngkjær, 2015), and effector gene expression (Banta et al., 1998). The hypothesis of temperature‐mediated Avr3a fitness is supported by significant associations of isoform frequency with the mean annual temperature in the sample sites (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…• Menna et al (2015) reported that elevated temperature altered resistance and HR in quantitatively different and genotype-dependent ways. • The TIR-NBS-LRR protein RPS6 confers resistance to P. syringae without visible cell death (Gassmann, 2005;Kim et al, 2009).…”
Section: Co N S E Q U E N C E S Resistancementioning
confidence: 99%
“…ETI suppression at high temperatures seems to be a genetically underpinned and adaptive trait, given the natural variations in A. thaliana for the temperature sensitivity of ETI (Menna et al ., ). Temperature‐sensitive components include NLR proteins themselves: NLR accumulation or nuclear localization is often reduced at high temperatures (Alcázar & Parker, ).…”
Section: Environmental Effects On Plant Immunitymentioning
confidence: 99%